Funcional independence of individuals With paraplegia in a rehabilitation program: results and associated factors - Gelson Aguiar da Silva (2006)
Spinal cord injury can convey constraints to individuals, but a rehabilitation program which evalueates the functional gain allows outpatient care during the rehabilitation process. The aim of the present research was to evaluate results obtained trough the administration of Functional Independence Measure (FIM scale) in paraplegic petients within rehabilitation programs, by connecting such results with the variables: age, gender, time, level and etiology of the lesion, classification of lesion according to the ASIA (American Spinal Injury Association) criterion, time of hosptalization, educational status and complications (pressure sores, heterotopic ossofication, spasticity and neuropathic pain). For such, a transversal quantitative retrospective descriptive study was proceeded by analyzing medical records and the scoresobtained with FIM scale. The investigations were done using spedific tests, through the SPOSS software (statistical Package for the Social Science), version 13 for Windws. Results demonstrated that among the variables there studied variables there is a direct correlation between age, time of lesion, motor level, time of hospitalization and hospitalization wich a companion and the independence gain (P< 0.05). Besides there is an inverse relation between the lession classification (AIS A, B, C, D, or E) and the functional gain (P< 0.05). Functional evaluation of people with spinal cord injury though MIF scale allows to fallow up functional gain in people within a rehabilitation program.